Gestão democrática: desafios e possibilidades dos conselhos de classe participativos e seus estranhamentos no contexto escolar - Gosenheimer, Sandra Mara (2024)
This dissertation was developed within the scope of the Postgraduate Program in Education, of the Institute of Humanities, Sciences, Education and Creativity, of the University of Passo Fundo (IHCEC/UPF), in the line of Educational Policies. Its object of study is Democratic Management, the challenges and possibilities of the Participatory Class Council, as well as its strangeness in the school context, in its relationship with the evaluation of the teaching and learning process. The research was carried out based on a qualitative approach, through the document analysis procedure in three state public schools of the Regional Education Coordination of Concórdia-SC. The general objective of the research was to analyze the Participatory Class Council and its relationship with evaluation and democratic management. The dissertation was organized and structured into five chapters. The first deals with introductory considerations. The second, entitled Democracy in public schools, addresses the importance of democratic participation in schools and the role of the principal in managing the Administrative, Physical, Financial and Pedagogical dimensions. To develop this chapter, authors such as Ângela Imaculada Loureiro de Freitas Dalben, Juan Enrique Díaz Bordenave, Cipriano Carlos Luckesi, Vitor Henrique Paro, José Carlos Libâneo and others were used. The third chapter, called Participatory Class Council: democratic space for estrangement in the school context, analyzes the Class Council and is based on documentary research based on legislation relating to the evaluation of state public schools in Santa Catarina. It analyzes the Political Pedagogical Project (PPP) and the democratic theories and practices that guide the instance of the Participatory Class Council (CCP). The fourth chapter, entitled Analysis of democratic management in the participatory Class Council of the researched schools, focuses on the Participatory Class Council and evaluation in the researched schools, as well as its importance in teaching and learning. The fifth chapter encompassed Final Considerations . From the research carried out, it was concluded that democratic management materializes in schools and the documents analyzed indicate practices and mechanisms that highlight the relevance of participation and dialogue with the representation of all segments of the institution in order to deliberate problem solutions. Everyone's co-responsibility was noted in contributing to the school fulfilling its social function, as well as its role in school evaluation and its importance in the teaching and learning process. Finally, the relevance of democratic management being based on State policies was highlighted, the continuity of which is marked by participation, dialogue, collective decision-making and permanent learning for those who participate in it.